Activity associated with stream segregation in human auditory cortex is similar for spatial and pitch cues - Schadwinkel, Stefan; Gutschalk, Alexander (Cerebral cortex, 2010)
Streaming is a perceptual mechanism by which the brain segregates information from multiple sound sources in our environment and assigns them to distinct auditory streams. Examples for streaming cues are differences in frequency spectrum, pitch, or space, and potential neural correlates for streaming based on spectral and pitch cues have been identified in the auditory cortex. Here, magnetoencephalography (MEG) and functional magnetic resonance imaging (fMRI) were used to evaluate if response enhancement in auditory cortex associated with streaming represents a general pattern that is independent of the stimulus cue. Interaural time differences (ITDs) were used as a spatial streaming cue and were compared with streaming based on fundamental frequency (f0) differences. The MEG results showed enhancement of the P1m after 60-90 ms that was similar during streaming based on ITD and pitch. Sustained fMRI activity was enhanced at identical sites in Heschl's gyrus and planum temporale for both cues; no topographical specificity for space or pitch was found for the streaming-associated enhancement. These results support the hypothesis of an early convergence of the neural representation for auditory streams that is independent of the acoustic cue that the streaming is based on.